Belarus in self-imposed isolation: Conflict with Poland and other neighbors poses security problems for the European Union - Rainer Lindner (Stiftung Wissenschaft und Politik (SWP), 2005)
Belarus exacerbated its self-imposed international isolation during summer 2005. Poland suspended relations in response to the expulsion of Polish diplomats and attacks on members of the Polish minority. Alexander Lukashenko has maneuvered his autocratic system into diplomatic quarantine with verbal invective against Lithuania, Latvia, Ukraine, and Georgia. Belarus's neighbors Ukraine, Poland, Lithuania, and Latvia have agreed to coordinate their policies toward the country, but the European Union still lacks a firm position, partly out of consideration for Russia. At the same time, relations between Belarus and the Russian Federation are also troubled. A conflict of more than merely regional scope is brewing on the Union's eastern border. (SWP-Comments / SWP)
Keywords: 320